Measuring the Level of Corona virus (COVID-19) Phobia: A cross - cultural study in the light of some variables (Journal of the College of Education for Women, 2024)
The objective of the current research is to measure the level of phobias from the emerging corona virus (Covid-19) among individuals in the Arab environment in both United Arab Emirates and Iraq. The researchers used the descriptive analytical approach on a sample consisting of (561) participants (volunteers); (409) from Iraq (73%) and (151) from United Arab Emirates (27%) of the total sample, (63%) females, and (37%) males. The Corona virus phobia scale (prepared by researchers) was applied. The scale consists of (39) items that include three basic areas: Fear of the future (18) items, general anxiety (15) items, and obsessive-compulsive disorder (6) items.The results indicated that (82%(of the study sample suffer from a high degree of anxiety about infection with the Corona virus. The results indicated that there are differences in the degree of Corona phobia between individuals in Iraq and United Arab Emirates in favor of individuals from Iraq, who have high degree of anxiety and fear of being infected by the virus. The results also showed that there are no significant differences in the phobia of infection with the Corona virus that are attributed to gender, marital status, level of education, and profession. The study recommended directing the attention of governments and various institutions in both countries to the importance of providing health support and working to improve the level of mental health so that individual citizens can be able to adapt to different life variables.